Value based capacity building through e-administration - Sharma, Sangeeta (2009)
The concept of Public Private Partnership (PPP) has transformed the vision of new government with more effective core content of humane governance. the productivity of system can only be enhanced when two divergent formats - one of welfarism, another of efficiency converges into a hybrid concept, which combines constructive dimensions of both. However effective and efficient system of governance without value-based capacities will not contribute to the social harmony. This article explores a new role carved for PPP alliance to build values by constructing a normative model. It follows a scientific expression that begins with certain premises and then subsequently brings out logical sequence to draw pointed conclusions. - Reproduced.
Keywords: E governance; Public private partnership